Combined Omics Approaches Reveal the Roles of Non-canonical WNT7B Signaling and YY1 in the Proliferation of Human Pancreatic Progenitor Cells. Issue 12 (17th December 2020) - Kimura, Azuma; Toyoda, Taro; Iwasaki, Mio; Hirama, Ryusuke; Osafune, Kenji
Summary: The proliferation of human pancreatic progenitor cells (PPCs) is critical for developing cell therapies for diabetes. Here, using transcriptome analysis combined with small interfering RNA (siRNA) screening, we revealed that WNT7B is a downstream growth factor of AT7867, a compound known to promote the proliferation of PPCs generated from human pluripotent stem cells. Feeder cell lines stably expressing mouse Wnt7a or Wnt7b, but not other Wnts, enhanced PPC proliferation in the absence of AT7867. Importantly, Wnt7a/b ligands did not activate the canonical Wnt pathway, and PPC proliferation depended on the non-canonical Wnt/PKC pathway. A comparison of the phosphoproteome in response to AT7867 or a newly synthesized AT7867 derivative uncovered the function of YY1 as a transcriptional regulator of WNT7B . Overall, our data highlight unknown roles of non-canonical WNT7B/PKC signaling and YY1 in human PPC proliferation and will contribute to the stable supply of a cell source for pancreatic disease modeling and therapeutic applications. Graphical Abstract: Highlights: WNT7B knockdown blocks compound-induced PPC proliferation WNT7B-expressing feeder cells can induce PPC proliferation Non-canonical Wnt/PKC pathway mediates PPC proliferation YY1 phosphorylation regulates WNT7B expression in PPCs Abstract : The mechanism of pancreatic progenitor growth during organogenesis is incompletely understood. Kimura et al. uncover roles for non-canonical Wnt/PKC signaling pathway and YY1 in the proliferation of human pluripotent stem cell-derived pancreatic progenitor cells.